Goats are susceptible to Bubaline alphaherpesvirus 1 infection: Results of an experimental study. (February 2017) - Camero, M.; Larocca, V.; Losurdo, M.; Lorusso, E.; Patruno, G.; Staffa, V.N.; Martella, V.; Buonavoglia, C.; Tempesta, M.
Highlights: Susceptibility of goats to Bubaline herpesvirus 1 infection. Lack of clinical signs in goats after Bubaline herpesvirus 1 infection. Epidemiological importance and impact on herpesvirus circulation. Inclusion of goats in the control program. Abstract: Herpesvirus infections are generally subjected to strong host species restriction, although virological and serological investigations have revealed the possibility of cross-species infections in closely related animal species. In this study we evaluated susceptibility of goats to infection by Bubaline alphaherpesvirus 1 (BuHV-1). Four goats were inoculated intra-nasally with BuHV-1 and monitored clinically, virologically and serologically for 42 days. None of the goats displayed clinical signs although all the animals variably shed the virus by the nasal route during the first 12 days after infection. BuHV-1 was also detected in the white blood cells of two animals in the first week post infection. The results suggest that goats are susceptible to BuHV-1 infection and that they could play an epidemiological role in the circulation/transmission of the virus among domestic and wild ruminants and impact to some extent on the control plans for herpesviruses in cattle.